Topics in Modal Analysis & Testing, Volume 10 Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017 - Mains, Michael; Blough, J.R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Topics in Modal Analysis & Testing, Volume 10: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the tenth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Modal Analysis, including papers on: Operational Modal & Modal Analysis Applications Experimental Techniques Modal Analysis, Measurements & Parameter Estimation Modal Vectors & Modeling Basics of Modal Analysis Additive Manufacturing & Modal Testing of Printed Parts .
Chapter 1.Fluid-structure Interaction in a Labyrinth gas Seal Coupled to a Flexible Stator -- Chapter 2.Modal Analysis of Tower Crane with Cracks by the Dynamic Stiffness Method -- Chapter 3.High-Noise High-Speed Footage Data in Experimental Modal Analysis -- Chapter 4.Morlet-Wave Damping Identification - Application to High-Speed Video -- Chapter 5.Fluid-coupled Vibration Control Inspired by Dragonfly Wings -- Chapter 6.Improving Modal Parameter Estimation by Complementary Output-Output Relations -- Chapter 7.Operational Modal Analysis in Frequency Domain using Gaussian Mixture Models -- Chapter 8.Understanding Modal Vectors -- Chapter 9.Best Practices for Using Order-Based Modal Analysis for Industrial Applications -- Chapter 10. Could the Veering Phenomenon be a Mechanical Design Instrument? -- Chapter 11. Impulse Excitation of Piezoelectric Patch Actuators for Modal Analysis -- Chapter 12. Modal Parameter Estimation in Multi-patch Operational Modal Analysis: Perspectives and Approaches -- Chapter.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Solids; Civil engineering; Mechanical engineering; Multibody Systems and Mechanical Vibrations; Solid Mechanics; Civil Engineering; Mechanical Engineering